Выражение: (1-cos(2*x)+sin(2*x))/(1+cos(2*x)+sin(2*x))=t*g*a
Ответ: 1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)-t*g*a=0
Решаем по действиям:
1. (1-cos(2*x)+sin(2*x))/(1+cos(2*x)+sin(2*x))=1+(-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))
2. 1+(-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))=1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)
Решаем по шагам:
1. 1+(-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))-t*g*a=0
1.1. (1-cos(2*x)+sin(2*x))/(1+cos(2*x)+sin(2*x))=1+(-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))
2. 1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)-t*g*a=0
2.1. 1+(-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))=1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)
Решаем уравнение 1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)-t*g*a=0:
Тестовая функция, правильность не гарантируется
Решаем относительно g:
g=-(-1+2*cos(2*x)/(sin(2*x)+cos(2*x)+1))/t/a=(1-2*cos(2*x)/(sin(2*x)+cos(2*x)+1))/t/a=(1/t-2*cos(2*x)/(sin(2*x)+cos(2*x)+1)/t)/a=(1/t-2*cos(2*x)/(sin(2*x)*t+cos(2*x)*t+t))/a=1/t/a-2*cos(2*x)/(sin(2*x)*t+cos(2*x)*t+t)/a=1/t/a-2*cos(2*x)/(sin(2*x)*t*a+cos(2*x)*t*a+t*a).